A Novel Network-based Continuous-time Formulation for Process Scheduling - Gimenez, Diego Marcelo (2008)
We present a novel network-based continuous-time formulation for process scheduling that addresses multiple limitations of existing approaches. Specifically, it handles non-simultaneous transfers of input/output materials to/from processing units; it employs a more flexible time representation; and it explicitly accounts for unit connectivity. This is accomplished via the modelling of two key issues: (i) the state of a processing/storage unit, and (ii) the material transfer between processing and storage units. The proposed formulation allows us to model many complexities associated with process scheduling and obtain solutions to problems that cannot be addressed by existing methods.